Secagem de materiais pastosos e granulares no leito de jorro mecânico e convencional - Sousa, Robson Costa de (2017)
This study had the objective to assess the behavior of a mechanically spouted bed compared to a conventional spouted bed through attrition of particulate matter, thermal and mass analysis during water evaporation and through the drying of pastes and granular materials. Based on the obtained results, two mathematical models were applied to represent attrition, the CST model and the two-parameter diffusive model to describe the drying of the paste and grains, respectively. Therefore, a stainless steel spouted bed with cylindrical column of 0.95 m of height, 0.30 m of diameter, inferior and superior conical base (60° angle) with 0.30 m of diameter and 0.20 m of height. For the mechanically spouted bed dryer, a helical screw with the following measures was used: outside diameter of 0.01 m, length of 1 m, 0.70 m of spiral with diameter, and pitch of 0.0508 m. The attrition experiments were conducted with dolomite particles, and glass and alumina spheres. With the exception of the glass beads, there was attrition for the other particulate materials in both spouted beds; however, at larger proportions when the conventional set was used. It was also observed that attrition influenced the fluid dynamics of the conventional spouted bed. Of the models used, the one proposed by Gwyn (1969) provided acceptable predictions regarding the results observed in this study. For water evaporation, glass beads of 3.2 mm of diameter were used as inert particles. It was verified that operational variables (velocity, temperature and water flow) had direct influence on temperature and relative and absolute humidity of air at the outlet of the spouted bed. For the drying of pastes, skimmed milk and the glass beads employed in the water evaporation trials were used. The skimmed milk interfered in the circulation of inert particles, causing changes in the dimensionless pressure drop and air humidity at the outlet of the mechanically spouted bed dryer. Relative and absolute humidity as well as the moisture of the powder collected at the outlet of the cyclone were influenced by the operational variables. The results predicted by the CST model presented satisfactory agreement with the majority of results obtained in the skimmed milk drying experiments. When it comes to the drying of alumina spheres, the dimensionless data of grain moisture and of temperature and relative humidity of the fluid phase as a function of time were influenced by the operational conditions. The results predicted by the two-parameter mathematical model reached satisfactory accuracy regarding the observed data and allowed for a qualitative analysis of the drying operation. In general, all results obtained in this study showed behavior which is consistent with what has been observed in the literature.